Pengembangan Sarana Promosi Melalui Web di UMKM Ondomohen Pack - Widayat, Edy; Pamudi, Pamudi; Mardiana, Ninik (Universitas Nusantara PGRI Kediri, 2021)
UMKM Ondomohen Pack is located at Ketabang Ngemplak No. 30 Surabaya, a micro business which is engaged in producing cardboard boxes made of paper that can be ordered in accordance with the wishes of the customer. This UMKM has problems in product marketing. Ondomohen Pack workers do not understand how the benefits of commercial web as a way of promotion in the digital world. Starting with discussion and observation, training and web management will be held. With the guided training method, direct training and indirect assistance (through social media). Finally, evaluation was conducted between the Unitomo lecturer team and work partners. The results and outcomes obtained are employees assigned to take care of the web have knowledge of managing a commercial web, the existence of a web page with the address Ondomohenpack.biz.id.